PHYTOPLANKTON AND ZOOPLANKTON ABUNDANCE IN AMBON BAY - Sutomo, -; Anderson, James Jay (Marine Research in Indonesia, 1984)
Ambon Bay has a shallow neritic inner bay and a deep oceanic outer bay. Net hauls suggest the inner bay has a large population of large phytoplankton cells but a small population of macrozooplankton. In the outer bay the opposite situation exists, with a greater population of macrozooplankton and smaller population levels of small phytoplankton. The differences might be caused by nutrient pollution and siltation in the inner bay.